Thermocatalytic pyrolysis of low-value waste biomass: Thermal decomposition, kinetics behaviour, and biochar characterization - Ranjeet Kumar Mishra; Sampath Chinnam; Abhishek Sharma (Results in Engineering)
This study investigates the pyrolysis behaviour of peanut shell waste (PNS) and the resulting biochar in the presence of calcium oxide (CaO). The pyrolysis test of PNS was carried out in a fixed-bed vertical reactor at 600 °C, with a heating rate of 5 °C min⁻¹ and a holding time of 30 min. Catalytic pyrolysis experiments were conducted using CaO at 5 and 10 wt.%, respectively. The kinetic analysis was performed using the Vyazovkin method (VZ) at dynamic heating rates of 10, 20, and 30 °C min⁻¹, revealing that activation energy varied with the degree of conversion. The physicochemical characterisation of PNS confirmed its suitability as an efficient pyrolysis feedstock. TGA-FTIR analysis demonstrated that CaO addition significantly reduced emissions of CO, CO₂, ether, and carbonyl compounds. Further, the addition of CaO increased biochar yield by approximately 6.5 % due to enhanced carbonation reactions. The untreated biochar exhibited a surface area of 113.40 m² g⁻¹, while biochar was produced with 5 and 10 wt.% CaO had reduced surface areas of 78.18 m² g⁻¹ and 51.55 m² g⁻¹, respectively. SEM analysis revealed altered surface morphology and reduced pore sizes caused by swelling and melting. FTIR analysis indicated a decrease in oxygenated functional groups in biochar with CaO addition. Furthermore, elemental and EDS analyses revealed a reduction in carbon content and an increase in oxygen content. Additionally, CaO incorporation increased biochar bulk density but reduced its higher heating value (HHV) due to changes in elemental composition. Finally, Raman spectroscopy indicated a decline in graphitic content with the addition of CaO.